50 χρόνια ΕΜΝΕ: Διάλογος για την ιστορία - ΚΑΡΑΜΑΝΩΛΑΚΗΣ, ΒΑΓΓΕΛΗΣ; ΑΒΔΕΛΑ, ΕΦΗ; ΛΙΑΚΟΣ, ΑΝΤΩΝΗΣ; ΠΟΛΙΤΗΣ, ΑΛΕΞΗΣ; ΜΑΤΘΑΙΟΥ, ΣΟΦΙΑ; ΜΙΧΑΗΛΑΡΗΣ, ΠΑΝΑΓΙΩΤΗΣ Δ.; ΠΟΛΕΜΗ, ΠΟΠΗ; ΤΡΙΑΝΤΑΦΥΛΛΟΥ, ΧΡΗΣΤΟΣ; ΧΑΤΖΗΙΩΑΝΝΟΥ, ΜΑΡΙΑ ΧΡΙΣΤΙΝΑ; ΔΗΜΗΤΡΙΑΔΗΣ, ΣΑΚΗΣ; ΚΟΛΟΒΟΣ, ΗΛΙΑΣ; ΚΥΡΑΜΑΡΓΙΟΥ, ΕΛΕΝΗ; et al. (Μνήμων, 2025)
-